Thermal management of vehicle radiator by nanofluid - Kadirgama, Kumaran
The excess heat produced in an internal combustion engine is removed by mean of an automotive cooling system. A literature survey shows that improvement on fins and microchannel in the radiator already reaches it limitation and any further modification would not make any difference. On the other hand, it is reported that conventional thermal transport fluid has poor thermophysical property and another reason for low heat dissipation from engine. Thus, demand for thermal transport fluid with high thermophysical property is increasing as it able to enhance heat transfer performance. Besides, by using an improved thermal transport fluid, size of the radiator could be miniaturized which also reduces weight of the vehicle. Literally, it helps to improve engine performance of vehicle. Few decades ago, nanofluid is widely have been researched to be used in heat transport applications. Nanofluid is prepared by dispersing nano-scaled material into a basefluid which enhances thermophysical property. In this research, nanosubstance used was nanocellulose extracted from Western Hemlock plant at weight concentration of 8.0% to be used as novel thermal transport fluid in radiator. The nanosubstance is dispersed into ethylene glycol-distilled water mixture at volume ratio of 40:60, respectively. Heat transfer performance of nanofluid and conventional ethylene glycol-water mixture is compared in a fabricated radiator test rig. Nanofluid is prepared by using two-step preparation method. Stability of nanofluid is evaluated through qualitative and quantitative method. The stability results prove that nanofluid can be stable for more than a month. Thermophysical property measurement for nanofluid is measured for volume concentration of 0.1, 0.5, 0.9 and 1.3% at temperature ranged from 30oC to 80oC. Analysis from statistical tool shows that volume concentration 0.5% has an optimized thermophysical property and it had been used as nanofluid (thermal transport fluid) in radiator. Then, experiment for heat transfer performance comparison for nanofluid and conventional thermal transport fluid is conducted in the automotive radiator test rig. Experiment for heat transfer analysis is conducted under two different circumstances; without the influence of draft fan and with the influence of draft fan. The experiment result shows that experimental heat transfer coefficient, convective heat transfer, Reynolds number, Nusselt number has proportional relation with volumetric flow rate. Meanwhile, friction factor has inverse relation with the volumetric flow rate. Maximum convective heat transfer enhancement recorded is 66.85% for without the influence of fan circumstance and 55.27% with the influence of fan circumstance. Thus, nanofluid able to remove heat efficiently in automotive cooling system. On the other side, maximum heat transfer enhancement involving ratio of convective heat transfer against conductive heat transfer in radiator is 39.75% for without the influence of draft fan circumstance and 43.24% with the influence of fan circumstance. Besides, maximum thermal and hydraulic performance factor without and with the influence of fan is 2.15 and 2.28 respectively. Thus, nanocellulose based nanofluid is suitable for automotive cooling application since it has a better heat transfer performance than conventional thermal transport fluid.